A aplicabilidade dos princípios da justiça restaurativa ao processo penal tradicional e à execução penal: o resgate da autonomia individual - Simões, Felipe Monteiro Batista (2025)
The research aims to analyze how the precepts, values and practices of Restorative Justice might contribute to the development of an intervention project in criminal execution, especially in women's prisons. The problem to be addressed is an apparent conflict that emerges from Criminology studies: on one hand, this science leads to the conclusion that it is impossible to use or reform criminal law and prison sentences to promote the peaceful reintegration of the convicted individual into society (the so-called resocialization). On the other hand, it demands the development of projects that are capable of addressing the harm caused by prisons to their inmates and to society, with the additional challenge of avoiding a new legitimization of prisons (which would amplify their use), or the increase in the vulnerability of inmates and ex-prisoners. This challenge is heightened when it comes to women's prisons, establishments that have a different genesis from male penal establishments. This is because the study of the subject “Human Rights of Vulnerable People in Perspective”, taught in this master's program leads to the analysis that, in these institutions, female inmates are exposed to an overlapping set of sociological, relational and ontological vulnerabilities, resulting both from their social condition as prisoners and from their gender (and, for many, from their race). For this reason, incarcerated women are among the groups in society most exposed to harm and violation of rights. The central hypothesis, developed from studies on Restorative Justice within the sphere of this master's program is that Restorative Justice's focus on empowerment, accountability, reparation and autonomy of the parties has the potential, when applied to prison and the period after the release of inmates, to mitigate their harm, without necessarily contributing to legitimizing retributive criminal law. Furthermore, by placing the needs of the involved people at the center of its dynamics, Restorative Justice also has the potential to illuminate and address the specific needs of women incarcerated in women's prisons, which tend to be marginal in the studies and debates about prisons.The research will be qualitative, based on semi-structured interviews conducted with former inmates of the Women's Prison located in Nossa Senhora do Socorro/SE, bibliographic and documentary research, as well as critical analysis of narratives collected in prison literature about the inmates' experience.